Theatre and Its Other Abhinavagupta on Dance and Dramatic Acting - Ganser, Elisa (Gonda Indological Studies, 2022)
In Theatre and Its Other, Elisa Ganser revisits a telling debate on the intertwined natures of dance and dramatic acting; preserved in Abhinavagupta's eleventh-century commentary on the Nāṭyaśāstra, it reflects complex historical shifts in aesthetic theory and performance practice. ; Readership: All those interested in the history of Indian dance and theatre and in Abhinavagupta's aesthetics, including scholars and students of Indology, performance, dance, and theatre studies, as well as performers.